136 EXTENSIVE BONE MARROW NECROSIS WITH RECOVERY. (1st January 2005) - Morris, D.; Elkins, S.
Abstract : Case Presentation: A 69-year-old white male presented to a local hospital with a two week history of hip pain, diarrhea, subjective fevers, and a fifteen pound weight loss. Additional symptoms of nausea, vomiting, and chest pain were present for one day. Physical examination was within normal limits. Lab results showed a WBC count of 40, 000, a platelets 71, 000, and a hematocrit of 39; other labs were normal except for an alkaline phosphatase of 217 and LDH of 556. His peripheral smear demonstrated no malignant cells. Two bone marrows only yielded necrotic tissue. Empiric antimicrobial therapy was initiated for persistent fever. He rapidly developed pancytopenia and was subsequently transferred for further evaluation and treatment. Diagnostic Evaluation/Hospital Course: Serologic studies for hepatitis, HIV, syphilis, histoplasmosis, blastomycosis, coccidioides, Aspergillus, Leptospira, Brucella, Cryptococcus, R. rickettsii, R. typhi, Q fever, and Bartonella were negative, as were blood cultures, stool studies, and sputum for AFB. A metastatic bone survey was negative, as were CT scans of the chest, abdomen, and pelvis. The patient subsequently developed herpetic lesions of upper lip and tongue that were confirmed by direct immunofluorescent staining, and acyclovir was started. He remained bedridden due to severe hip and back pain. Transfusions were administered as needed. After four weeks his counts gradually improved and were near normal within six weeks. MRI of the spine and hips demonstrated areas consistent with persistent necrosis in addition to diffuse areas of enhancement consistent with marrow replacement. Viable marrow was obtained and significant for areas of 100% cellularity adjacent to necrotic tissue. There was normal trilineage maturation with no evidence of malignancy. Flow cytometry, chromosomal analysis, and FISH for the BCR-ABL translocation of the marrow were all within normal limits. He was subsequently transferred to a rehabilitation facility without a clear the etiology of his bone marrow necrosis. Discussion: Necrosis of the bone marrow is characterized by destruction of the medullary stroma and gelatinous transformation. A malignancy is present in approximately 90% of cases, most often being hematological. Other associations include sickle cell disease, infections, and medications. The most commonly reported symptoms are fever and pain that may be severe and debilitating. Anemia and thrombocytopenia are typically present at presentation, while the WBC count may be elevated or decreased.